In Situ Absorption Characterization Guided Slot‐Die‐Coated High‐Performance Large‐Area Flexible Organic Solar Cells and Modules. Issue 10 (22nd January 2023) - Shen, Yi‐Fan; Zhang, Hao; Zhang, Jianqi; Tian, Chenyang; Shi, Yanan; Qiu, Dingding; Zhang, Ziqi; Lu, Kun; Wei, Zhixiang
Abstract: Slot‐die coating is recognized as the most compatible method for the roll‐to‐roll (R2R) processing of large‐area flexible organic solar cells (OSCs). However, the photovoltaic performance of large‐area flexible OSC lags significantly behind that of traditional spin‐coating devices. In this work, two acceptors, Qx‐1 and Qx‐2, show quite different film‐formation kinetics in the slot‐die coating process. In situ absorption spectroscopy indicates that the excessive crystallinity of Qx‐2 provides early phase separation and early aggregation, resulting in oversized crystal domains. Consequently, the PM6:Qx‐1‐based 1 cm 2 flexible device exhibits an excellent power conversion efficiency (PCE) of 13.70%, which is the best performance among the slot‐die‐coated flexible devices; in contrast, the PM6:Qx‐2 blend shows a pretty poor efficiency, which is lower than 1%. Moreover, the 30 cm 2 modules based on PM6:Qx‐1, containing six 5 cm 2 sub‐cells, exhibit a PCE of 12.20%. After being stored in a glove box for over 6000 h, the PCE remains at 103% of its initial values, indicating excellent shelf stability. Therefore, these results show a promising future strategy for the upscaling fabrication of flexible large‐area OSCs. Abstract : In situ absorption measurement is used to investigate the aggregation behavior of acceptors during slot‐die‐coating. The 1 cm 2 flexible device can reach a power conversion efficiency of 13.70%, with excellent shelf stability and upscaling ability. The connected modules (180 cm 2 ) can effectively power a smartphone, showing great potential for future applications.